Tingkatkan Literasi Keuangan Masyarakat Melalui Seminar Ekonomi Syariah - Sopian, Ahmad Ali (STIE Syariah Indonesia Purwakarta, 2022)
Islamic banking literacy is very important to be understood and owned by all levels of society in this modern era. The problems raised in this community service activity are the inequality of public information on Islamic banking products and the equality of Islamic banking products with conventional banking products. This PKM program aims to provide information on banking products that can be accessed to facilitate business development such as financing for MSME capital, motor vehicles, education and fund-raising programs such as savings and investment. The method used in this community service program is education and collaboration. Based on the implementation of the community service program, it can be concluded that the public better understands economic transactions that have the potential and contain elements of usury by strengthening the arguments and rules of fiqh; The public can carry out economic transactions without any doubt, both in business transactions and economic transactions related to Islamic financial institutions; The community is no longer mistaken and equates the quality of Islamic banking products and conventional banking products; Access to cooperation in fund storage programs for Village movers, MSME activists, Youth Organizations and ta'lim assemblies, as well as financing programs; and the community understands the importance of an education and efforts to practice the knowledge that has been taken.